Pengaruh good corporate governance terhadap kinerja karyawan di Rumah Sakit Akademis Jaury Jusuf Putera, Makassar - Rusydi, Arni Rizqiani; Arman, Arman; Hamzah, Fyrdha Faradyba (Universitas Aisyah Pringsewu, 2023)
This study aimed to analyze the impact of good corporate governance (GCG), encompassing transparency, accountability, responsibility, independence, and fairness, on employee performance at Jaury Jusuf Putera Academic Hospital, Makassar. Utilizing an analytical observational method with a cross-sectional study approach, the research was conducted in January 2023 with a sample size of 86 individuals out of 109 employees at Jaury Jusuf Putera Academic Hospital. Primary and secondary data were collected through questionnaires and analyzed using univariate, bivariate, and multivariate analyses, including tests for data normality and hypothesis testing. The results indicated that all GCG variables (transparency, accountability, responsibility, independence, and fairness) had a positive and significant influence on employee performance. This study confirms that the implementation of GCG principles can enhance employee performance, where employees operating in an environment characterized by transparency, accountability, responsibility, independence, and fairness tend to exhibit better performance. This conclusion underscores the importance of applying GCG in improving employee performance, especially in the healthcare sector such as hospitals.